Carbon capture and storage technologies in the European power market - Rolf Golombek; Finn Roar Aune; Mads Greaker; Sverre A.C Kittelsen; Ole Røgeberg (Statistics Norway, Research Department, 2009)
We examine the potential of Carbon Capture and Storage (CCS) technologies in the European electricity markets, assessing whether CCS technologies will reduce carbon emissions substantially in the absence of investment subsidies, and how the availability of CCS technologies may affect electricity prices and the amount of renewable electricity. To this end we augment a multi-market equilibrium model of the European energy markets with CCS electricity technologies. The CCS technologies are characterized by costs and technical efficiencies synthesized from a number of recent cost estimates and CCS technology reviews. Our simulations indicate that with realistic values for carbon prices, new CCS coal power plants become profitable, totally replacing non-CCS coal power investments and to a large extent replacing new wind power. New CCS gas power also becomes profitable, but does not replace non-CCS gas power fully. Substantially lower CCS costs, through subsidies on technological development or deployment, would be necessary to make CCS modification of old coal and gas power plants profitable.
Keywords: H23; Q40; Q54; 330; Carbon capture and storage; fossil fuels; energy; carbon emissions; abatement.